EVALUATE THE IMPACT OF PROVIDING SPECIAL FLAT HOUSES AT STISIPOL RAJA HAJI - Nurhadiyanti, Nurhadiyanti (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Ministry of Public Works and Public Housing provides Special Flats in universities, one of which is at STISIPOL Raja Haji. This research was conducted to determine the impact of the provision of STISIPOL Raja Haji Special Flats. There are six dimensions used in this study including, effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This type of research is evaluative with a quantitative approach. The data collection method is a questionnaire in the form of a questionnaire that is distributed directly to all residents. The population in this study was 31 people. Furthermore, the population as a whole becomes a study sample or saturated sampling (census). The result of the evaluation research on the provision of Special Flats at STISIPOL Raja Haji as a whole have been very good with a value of 86,00 or letter A. Meanwhile, for each dimension, effectiveness is 86.00 or letter A, efficiency is 83.60 or letter B, adequacy with a value of 89.00 or letter A, equitable distribution with a value of 86.20 or letter A, responsiveness with a value of 86.40 or letter A and accuracy of 86.40 or letter A. The first suggestion of this study to the Ministry of PUPR should continue construction of special flats with the same concept as at STISIPOL Raja Haji. Second, STISIPOL Raja Haji, who will then be the recipient of the grant, must be able to manage and utilize it. Third, residents of STISIPOL Raja Haji Special Flats must maintain the facilities that are already available.